HUBUNGAN USIA IBU DENGAN KEJADIAN BAYI LAHIR PREMATUR DIRUMAH SAKIT UMUM DAERAH SYEKH YUSUF KABUPATEN GOWA - Muhammad Syahrul Alam; Wiwiek Hidayati Jaya; Muhammad Iqbal (PT.Mantaya Idea Batara, 2024)
Preterm birth is the leading cause (60-80%) of neonatal morbidity and mortality worldwide. Every year, approximately 15 million babies are born prematurely in the world, more than one in 10 births. The aim of this study was to determine the relationship between maternal age and the incidence of prematurity at the Syekh Yusuf Regional Hospital, Gowa Regency. The design of this research is quantitative using an analytical survey method through a cross sectional approach where maternal age is the independent variable and the incidence of prematurity is the dependent variable. This research was carried out at the Syekh Yusuf Regional Hospital, Gowa Regency on 16 February – 10 March 2023. The population in this study were all mothers who gave birth at the Syekh Yusuf Regional Hospital, Gowa Regency with a total sample of 67 respondents obtained using random sampling techniques. The results of this study showed that of the 67 respondents there were 43 (64.2%) respondents who were at risk and experienced prematurity, 4 (6.0%) respondents who were not at risk and experienced prematurity, 6 (9.0%) respondents who were at risk age and did not experience premature events, and 14 (20.9%) respondents who were not at risk age and did not experience premature events. Based on the results of statistical tests using Chi Square with a significance level of ? = 0.05, the statistical test results were c2count > 2table or 26.998 > 3.84.